Gobernanza ambiental y desarrollo local: el caso de la RBMM en Michoacán - Gómez Mora, Alejandra (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
This work, we examined the contribution or contribution towards the local development resulting from the Decree of the reserve of the biosphere of the monarch butterfly (RBMM), in the State of Michoacán, in the Ejido El Rosario, Emiliano Zapata and hive and iron in the municipality of Ocampo. So, is is of respond would in what grade is based it management of the RBMM in Michoacan in the criteria of governance? and what qualitative contribution elements that indicate a local development in the zone?, how it can identify the environmental governance in the RBMM?, what is the relationship between environmental governance and local development?, how can include elements of environmental governance so it can favour local development?, and what are the elements of environmental governance that can help resolve the conflicts socio-environmental area?. It conducted a series of interviews and surveys in our study area during the months of April and may of 2016, to this end with our analysis and conclude the investigation; where it was found the hypothesis of this work, that the Decree of the ANP has enabled support in different spheres (environmental, social, institutional and economic) that can contribute to improving development in the aforementioned ejidos, however the RBMM operation management is not based on criteria of environmental governance, which limits local development.

En el presente trabajo, se analizó el aporte o contribución hacia el desarrollo local que conlleva el decreto de la Reserva de la Biosfera de la Mariposa Monarca (RBMM), en el estado de Michoacán, en los ejidos El Rosario, Emiliano Zapata y Hervidero y Plancha en el municipio de Ocampo. Así, se trata de responder ¿en qué grado se basa la gestión de la RBMM en Michoacán en los criterios de gobernanza? y ¿cuáles son los elementos cualitativos de aporte que indican un desarrollo local en la zona?, ¿de qué manera se puede identificar la gobernanza ambiental en la RBMM?, ¿cuál es la relación entre gobernanza ambiental y desarrollo local?, ¿cómo se pueden incluir los elementos de gobernanza ambiental para que se pueda favorecer el desarrollo local?, y ¿cuáles son los elementos de la gobernanza ambiental que pueden contribuir a solucionar los conflictos socioambientales en la zona?. Para ello se realizó una serie de entrevistas y encuestas en nuestra zona de estudio durante los meses de abril y mayo del 2016, para con ello finalizar con nuestro análisis y concluir la investigación; donde se comprobó la hipótesis de dicho trabajo, de que el decreto de esta ANP ha permitido el apoyo en diferentes esferas (ambiental, social, institucional y económica) que puede contribuir a mejorar el desarrollo en los ejidos mencionados, sin embargo la gestión de operación de la RBMM no está basada en criterios de gobernanza ambiental, lo cual limita el desarrollo local.
Facultad de Economía Vasco de Quiroga. Maestría en Ciencias en Desarrollo Local
Keywords: info:eu-repo/classification/cti/5; FEVAQ-M-2017-0240; Reserva; Mariposa monarca; México; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5010